Quantification of plasminogen activator inhibitor type 1 in the aortic wall - Kríková, V; Korabecná, M; Kocová, J; Treska, V; Molácek, J; Tonar, Z; Tolinger, P; Nedorost, L (International angiology, 2009)
AIM: Plasminogen activator inhibitor type 1 (PAI-1) plays a key role in regulation of fibrinolytic system, cell-associated proteolysis and migration of smooth muscle cells (SMC). This study is focused on the types of PAI-1 expressing cells, quantification of PAI-1 expression in the walls of aneurysmatic abdominal aortas (AAA) and correlation between histological and clinical findings. METHODS: A group of nine patients who underwent surgery for AAA: asymptomatic (aAAA), symptomatic (sAAA) and ruptured (rAAA) and one control specimen (CA) were included in the study. Samples underwent histological processing and immunohistochemistry in comparison with in situ hybridisation. In order to assess the PAI-1 area fraction in histological sections through the aortic wall the Line System module of Ellipse software was used. PAI-1 expressing cells were measured in CA and AAA: endothelium, SMC, and foam cells. Photomicrographs with a total area of 0.7 mm(2) for each specimen were analysed by two independent observers. Mean values of PAI-1 positive components per section area were calculated as average values. RESULTS: The results of both observers are as follows: 28.6% in CA; 18.1% in aAAA; 10.9% in sAAA; 11.0% in rAAA. During the progression of AAA, the SMC (PAI-1 expression was found mainly in them) became less abundant in agreement with the values of PAI-1 area fraction. In rAAA immunohistochemistry detected PAI-1 in necrotic centres of atheromathous plaques. CONCLUSIONS: AAA may be evaluated as the result of gradual changes in regulation of fibrinolysis that is observed as redistribution of cells expressing PAI-1. The area fraction of PAI-1 positive components correlates with clinical classification of AAA.
Keywords: dospělí; senioři nad 80 let; Aortic Aneurysm, Abdominal; aorta abdominalis; Humans; lidé středního věku; Middle Aged; Aged, 80 and over; Aorta, Abdominal; aneurysma břišní aorty; Plasminogen Activator Inhibitor 1; mužské pohlaví; Adult; inhibitor aktivátoru plazminogenu 1; ženské pohlaví; lidé; Aged; senioři; Male; Female